IMPLEMENTASI NILAI SUNNAH NABI PADA ANAK-ANAK DI TADIKA RAUDHAH BARA’QINUL EIMAN (RBE) PRESCHOOL, PENANG, MALAYSIA - Puspita Sari, Dila; Munawir Pasaribu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates how young children at Tadika Raudhah Bara'qinul Eiman (RBE) Preschool in Penang, Malaysia, use the principles of the Prophet's Sunnah. In August 2025, semi-structured teacher interviews, participant observation, and documentation analysis were used to gather data using a qualitative descriptive technique. The results show that through habituation, role modeling, and organized play-based activities, fundamental Sunnah values such as eating and drinking while seated, using courteous expressions (such as "please," "sorry," "thank you," and "excuse me"), honesty, and compassion are methodically incorporated into daily routines. While active parental participation via communication platforms like WhatsApp groups fosters consistency between the home and school environments, teachers operate as the main role models. While problems include variable parental engagement and inconsistent kid responsiveness, supporting elements include a supportive Islamic environment and consistent guidance. The study comes to the conclusion that this preschool's Sunnah-based character education successfully promotes the development of early Islamic personalities and provides a model that other Islamic early childhood institutions might follow. This study adds to the body of knowledge on Sunnah-based moral teaching both conceptually and practically by offering parents and teachers useful tactics.